The importance of immunological analysis in the prevention of the development of familial asthma in the Uzbek population - Okboev T.A. (American Journal of Bioscience and Clinical Integrity, 2024)
The article examines the importance of serum immunoglobulin, anti-inflammatory, and enhancer cytokine spectrum in early detection and prevention of the risk factor that triggers the development of the disease in familial bronchial asthma. The study was conducted in 346 relatives in 49 families with bronchial asthma. This examined total serum IgE, IL-6 and interferon-g using the "Vector-Best" test-system according to the IFA method. Total serum IgE, IL-6, and interferon-g levels of patients with familial asthma have been analyzed for pathogenetic types of bronchial asthma disease, disease spikes, disease seniority, and disease control rates. In this case, it has been shown that different manifestations of familial asthma at the control level of withdrawal steps, types, duration of the disease and the amount of total IgE, IL-6, interferon-g are important in the prevention and early diagnosis of risk factors that cause the development of the disease in the family.